Wage determination and the sources of bargaining power - Paola Manzini; Dennis J. Snower (Institute for the Study of Labor (IZA), 2002)
This paper explores the sources of bargaining power in wage negotiations. In the standard analyses of wage bargaining, the negotiation partners are specified a priori, and thus it is impossible to address the question of how they achieve and retain their negotiating positions, on which their bargaining power is based. In our analysis, by contrast, the firm can choose between two sets of wage negotiations: those it can conduct with its incumbent employees and those with new job seekers. These negotiations are imperfectly substitutable, and the degree of substitutability is determined by the firm's labor turnover costs (e.g. costs of hiring, training, and firing). In this context, labor turnover costs not only influence the negotiators? alternative to bargaining (i.e. their fall-back positions and outside options); they affect the nature of the bargaining process itself. This approach leads to a new theory of wage determination.
Keywords: J31; J32; C76; 330; wage determination; labor turnover costs; credibility; bonding; churning; bargaining; Lohntheorie; Lohnverhandlungstheorie; Insider-Outsider-Modell; Arbeitsmobilität; Kündigung; Kosten; Theorie